Lessons from the Bay of Bengal ITLOS case: stepping offshore for a 'deeper' maritime political geography. Issue 3 (12th December 2013) - Lin, Shaun; Schofield, Clive
<x xml:space="preserve">Abstract</x> On 14 March 2012, the International Tribunal for Law of the Sea (ITLOS) delimited a maritime boundary with respect to multiple distinct maritime jurisdictional zones (territorial sea, exclusive economic zone and continental shelf) between Bangladesh and Myanmar (Bay of Bengal Case). ITLOS did not, however, wholly resolve the issues of marine governance that the two states face in the Bay of Bengal, leaving a number of complex and potentially problematic issues outstanding, including the unique creation of what was termed a 'grey area', the governance arrangements for which are open to debate. This commentary highlights future opportunities of research on the outer continental shelf and the grey area in political geography.